Examining The Impact of Socioeconomic Status Factors on Happiness Levels in Indonesia - Indriana, Intan Solikhah; Hartarto, Romi Bhakti; Putri, Ananda Raissa (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2024)
This research aims to investigate the impact of socioeconomic status factors on individual happiness in Indonesia. Happiness is a multifaceted phenomenon arising from both internal and external sources. While conventional measures often reduce it to mere absolute income, a comprehensive understanding necessitates the incorporation of subjective perspectives. Our study unveils compelling insights into the impact of socioeconomic status on happiness. In doing so, this research contributes valuable insights to the field of happiness economics. It informs policy initiatives to enhance the well-being of individuals in Indonesia and similar contexts.Â Drawing upon cross-sectional data from the Indonesian Family Life Survey, Wave 5 (2014), encompassing a substantial sample of 29,018 respondents, we employ the ordered probit method. This statistical choice is motivated by the ordinal nature of the response variable and its alignment with normality assumptions in error distribution. The research findings reveal several socioeconomic status factors that significantly influence happiness. Wealth level, education, urban residence, and religion correlate positively with individual happiness, while age and employment status show a negative correlation. Conclusion: These findings underscore the importance of socioeconomic policies to enhance the happiness of Indonesian society.